A Xanthomonas citri subsp citri hypothetical protein related to virulence contains a non-functional HD domain and is implicated in flagellar motility - Vieira, F. C. F. [UNESP]; Goncalves, A. M. [UNESP]; Mendoza, E. F. R. [UNESP]; Ferreira, R. M. [UNESP]; Costa, M. L. M. [UNESP]; Balbuena, T. S. [UNESP]; Sebinelli, H. G.; Ciancaglini, P.; Pizauro Junior, J. M. [UNESP]; Ferro, J. A. [UNESP] (Funpec-editora, 2017)
Citrus canker, caused by the Gram-negative bacterium Xanthomonas citri subsp citri (Xac), severely affects most economically important citrus varieties worldwide. A previous study showed that disruption of the ORF XAC1201 from the Xac 306 strain by transposon Tn5 decreased bacterium virulence in the Rangpur lime host (Citrus limonia L. Osbeck). However, little is known regarding the possible function of the hypothetical protein XAC1201 and how it affects the virulence of Xac 306. Here, we confirmed that disruption of ORF XAC1201 reduces Xac 306 virulence in two different hosts, delaying the onset of typical symptoms. In silico analysis suggested that XAC1201 interacts with the flagellar proteins FliM and FliL, known to be an important factor for virulence. In fact, motility assays revealed that the XAC1201 mutant has a significant difference in motility compared to the wild-type Xac 306. Also, a 3-D structure model revealed modified cofactor binding sites and suggested that XAC1201 has a non-functional HD domain. This hypothesis was confirmed by enzymatic assays performed in purified, XAC1201 recombinant protein expressed in Escherichia coli, which revealed no significant activities previously associated with HD domains for the tested substrates. Thus, the role of the XAC1201 protein in Xac 306 virulence seems to be related to flagellar motility, although a non-classic role for the HD domain cannot be dismissed.
Keywords: Citrus canker; ORF XAC1201; Motility; HD domain; Bacterial flagella